2022
DOI: 10.1029/2021gl096938
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Biogeochemical Signatures of the North Pacific Blob

Abstract: The Blob was the early manifestation of the Northeast Pacific marine heat wave from 2013 to 2016. While the upper ocean temperature in the Blob has been well described, the impacts on marine biogeochemistry have not been fully studied. Here, we characterize and develop understanding of Eastern North Pacific upper ocean biogeochemical properties during the Winter of 2013–2014 using in situ observations, an observation‐based product, and reconstructions from a collection of ocean models. We find that the Blob is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 49 publications
(68 reference statements)
6
17
0
Order By: Relevance
“…The “Blob,” a prolonged and extensive marine heatwave that occurred from 2013 to 2015 in the Northeast Pacific, illustrates the potential threat posed by marine compound events on ecosystems. This marine heatwave coincided with anomalously low oxygen, low pH, and large negative anomalies in phytoplankton NPP (Gruber et al, 2021; Le Grix et al, 2021; Mogen et al, 2022; Whitney, 2015; Wyatt et al, 2022), leading to severe impacts on marine life (Cavole et al, 2016), including mortality and reproductive failure of sea birds (Jones et al, 2018; Piatt et al, 2020), mass strandings of sea lions in California and of whales in the western Gulf of Alaska (Cavole et al, 2016), as well as shifts in species distribution toward warm‐water species, with repercussions on fisheries (Cavole et al, 2016; Cheung & Frölicher, 2020). Previous research has shown that marine heatwaves and compound extreme events have become more frequent over the past century (Gruber et al, 2021; Oliver et al, 2018) and that this trend is projected to continue as global warming persists (e.g., Burger et al, 2022; Frölicher et al, 2018).…”
Section: Introductionmentioning
confidence: 91%
“…The “Blob,” a prolonged and extensive marine heatwave that occurred from 2013 to 2015 in the Northeast Pacific, illustrates the potential threat posed by marine compound events on ecosystems. This marine heatwave coincided with anomalously low oxygen, low pH, and large negative anomalies in phytoplankton NPP (Gruber et al, 2021; Le Grix et al, 2021; Mogen et al, 2022; Whitney, 2015; Wyatt et al, 2022), leading to severe impacts on marine life (Cavole et al, 2016), including mortality and reproductive failure of sea birds (Jones et al, 2018; Piatt et al, 2020), mass strandings of sea lions in California and of whales in the western Gulf of Alaska (Cavole et al, 2016), as well as shifts in species distribution toward warm‐water species, with repercussions on fisheries (Cavole et al, 2016; Cheung & Frölicher, 2020). Previous research has shown that marine heatwaves and compound extreme events have become more frequent over the past century (Gruber et al, 2021; Oliver et al, 2018) and that this trend is projected to continue as global warming persists (e.g., Burger et al, 2022; Frölicher et al, 2018).…”
Section: Introductionmentioning
confidence: 91%
“…Here, we demonstrate the ability to predict short-term variations in the state of marine stressors, but our results also suggest that there may be potential for forecasting extreme events. Marine heatwaves, for example, can have profound impacts on biogeochemistry throughout the water column Mogen et al, 2022). Prior work has demonstrated that dynamical, initialized modelling systems can effectively predict heatwaves , but has not examined the potential co-occuring bio-geochemical effects which often interact with warm temperatures to redistribute species and affect human uses of the ocean.…”
Section: D) E) F ) G) H) I) J) K) L) M) N) O) P) Q) R)mentioning
confidence: 99%
“…The global ocean is facing growing threats from the accumulation of excess heat and carbon dioxide in the Earth System, leading to ocean warming, acidification, and deoxygenation (Bopp et al, 2013;Doney et al, 2009;. On top of long-term trends, climate variability and extremes on shorter timescales can rapidly alter temperature and have major effects on regional biogeochemistry (Di Mogen et al, 2022). Since marine organisms and ecosystems are highly sensitive to changes in their environment across a range of timescales, climate variability and trends will likely alter their success and spatial distribution Doney et al, 2009;, which is of great concern for fisheries and aquaculture systems .…”
Section: Introductionmentioning
confidence: 99%
“…This persistently cohesive and anomalously warm body of water, first detected in the sub-polar northern Pacific in late 2013, expanded in 2014 to encompass almost the entire west coast of North America, with sea surface temperatures reaching 2.5-3.0 o C above average. The marine heat wave (MHW) persisted from 2013 to 2016 in some coastal areas (Mogen et al, 2022). It has been speculated that the warm temperatures had a detrimental effect on kelp density and productivity, with greater severity in northern California compared to central and southern areas (Rogers-Bennett and Catton, 2019).…”
Section: Current Statementioning
confidence: 99%